Adoption of the Electronic Labour eXchange : an archival research of an e-Government Pilot Project / Azam Amaluddin - Amaluddin, Azam (2005)
The Electronic Labour eXchange (ELX) is an e-Government pilot project, which is one of the Multimedia Super Corridor (MSC) flagship applications. Unfortunately, it has suffered poor promotional efforts, and as a result, it does not live up to expectations. The research aims to propose a way to dramatically boost the adoption of the ELX among its key users whom would benefit the most from the exercise. By utilizing the Quantitative Positivist Research (QPR) methodology, an archival research was conducted on the database of the ELX to analyze huge amounts of data and hopefully discover a significant correlation that is both positive and strong. What the research has found is both alarming and relieving: the key users of the ELX are comprised of unemployed fresh graduates, confirming the severity of the unemployment problem within the nation, but also provides the best avenue to address the problem: at its source.